Factores de riesgo de la conducta delictiva de mujeres adolescentes - Cáceres, Joselin A. (2020)
Criminal behaviors in adolescent women have been little studied despite the fact that configure a problem that requires a broader analysis of the main causes that originate them. The study of risk factors, both individual and environmental / contextual in adolescence, will allow understanding the origin of development of antisocial and criminal behaviors in women who will not be the same as that are built from the masculine. Due to the great research limitations to national and international level in relation to gender, it becomes imperative to approach the different characteristics that intervene for female adolescents to immerse themselves in the world of crime. It is worth specifying that its lower incidence compared to the male population, cannot be ignored when establishing a classification of risk factors that in the near future will promote new studies investigations with a gender approach.